Motivational factors in sales team management and their influence on individual performance - Teresa Santos Ferreira (Tourism & Management Studies)
This study analysed the intrinsic and extrinsic motivational factors of sales teams and these factors’ influence on team members’ performance in a pharmaceutical industry context. A quantitative survey was conducted by distributing a questionnaire to a sample of 326 salespeople working in Portugal. The data were analysed using two statistical approaches: descriptive analysis of the variables and structural equation analysis. The results show that the intrinsic factors that best explain sales teams’ motivation are ‘personal goals’ and ‘skills acquired’. Extrinsic factors that best explain motivation in this context are ‘transparency and loyalty in interactions with bosses’ and ‘trust in the company’. ‘Participation in the growth of the company’s business’ and ‘attitude’ are the factors that most influence team performance in terms of results and behaviour, respectively